Gastric duplication in an adult mimicking mucinous cystadenoma of the pancreas. Issue 11 (27th October 2004) - D'Journo, X B; Moutardier, V; Turrini, O; Guiramand, J; Lelong, B; Pesenti, C; Monges, G; Giovannini, M; Delpero, J R
Abstract : Gastric duplication cyst (GDC) in an adult can have several clinical presentations. A review of the literature showed previously reported cases of GDC presenting as pancreatic pseudocyst or with greatly raised concentrations of carbohydrate antigen 19-9 (CA 19-9). It is often difficult to discriminate GDC from pancreatic cystic tumour, in particular pancreatic mucinous cystadenoma, in which concentrations of carcinoembryonic antigen and CA 19-9 are classically raised. This report describes an adult case of GDC mimicking a mucinous cystadenoma of the pancreas. This is the first report of a simultaneous increase in carcinoembryonic antigen and CA 19-9 in GDC in the absence of malignancy. Although few cases of carcinoma arising from a GDC having been reported, the production of oncofetal antigens raises the problem of a precancerous condition in long standing intestinal duplications. In this situation surgical resection must be performed.